A Comprehensive Systematic Review of Association of SGLT2 Inhibitors to Renal Protection in Patients with Diabetic Kidney Disease - Afrizal Adi Nugroho; Fatimah Yasin (International Medical Journal Corp. Ltd, 2026)
Introduction: Diabetic kidney disease (DKD) remains a leading cause of end-stage renal disease worldwide despite optimal renin-angiotensin-aldosterone system blockade. Sodium-glucose cotransporter 2 (SGLT2) inhibitors have emerged as potential renoprotective agents, yet the totality of evidence across diverse study designs, populations, and renal outcomes requires comprehensive synthesis. This systematic review aims to evaluate the association between SGLT2 inhibitors and renal protection in patients with DKD, synthesizing evidence from randomized controlled trials, observational studies, and meta-analyses. Methods: A comprehensive systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria including adult patients (≥18 years) with DKD, SGLT2 inhibitor intervention, renal outcomes reported (eGFR decline, albuminuria reduction, progression to ESRD), study designs including RCTs and observational studies, follow-up ≥12 weeks, and exclusion of case reports/series. Data extraction encompassed study characteristics, SGLT2 inhibitor details, population demographics, renal outcomes, effect sizes, mechanisms, and adverse effects. Methodological quality was assessed using Cochrane risk of bias tools and Newcastle-Ottawa Scale. Results: From the evidence base comprising over 90,000 participants across landmark trials (CREDENCE, DAPA-CKD, EMPA-KIDNEY) and numerous meta-analyses, SGLT2 inhibitors consistently demonstrated significant renal protection. Pooled analyses showed 30-40% risk reduction in composite renal outcomes (HR 0.61-0.71, 95% CI), 25-35% reduction in albuminuria progression, and 30% slower eGFR decline. Benefits were consistent across subgroups including baseline eGFR <30 mL/min/1.73m², elderly patients, and varying albuminuria levels. Hemodynamic mechanisms (reduced intraglomerular pressure via tubuloglomerular feedback) and metabolic effects (glycemic control, weight reduction) contributed independently of HbA1c changes. Safety analysis revealed initial eGFR dip (typically <5 mL/min/1.73m², reversible) without increased acute kidney injury risk; genital infections were increased but rarely severe. Discussion: This comprehensive synthesis confirms SGLT2 inhibitors as foundational therapy for renal protection in DKD, with benefits extending across CKD stages 2-4 and independent of diabetes duration or glycemic control. The consistency between RCT efficacy and real-world effectiveness supports broad implementation. Mechanisms involve hemodynamic normalization, anti-inflammatory effects, and improved mitochondrial function. Conclusion: SGLT2 inhibitors provide robust, multi-mechanistic renal protection in DKD with favorable safety profiles. We recommend their early initiation in DKD patients regardless of glycemic control, with monitoring for reversible eGFR decline and volume status. Future research should address optimal combination strategies with newer agents and long-term outcomes beyond five years.